PERBANDINGAN KINERJA KEUANGAN SEBELUM DAN SETELAH PENERAPAN AKUNTANSI SUMBER DAYA MANUSIA PADA PUSKOSIPA PHS SUMSEL - Msy. Mikial; Meti Zuliyana; Alfian . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2017)
This study discusses the comparison of financial performance before and after the application of ASDM. In this research, primary data source obtained directly from Puskosipa PHS Sumsel that is information about company policy related to recruitment and training cost, while secondary data obtained from brief history, organizational structure and financial report from January 2014 until December 2016. Data collection technique used are participant observation, interview and documentation. For data analysis technique use descriptive statistical test, normality test and paired sample test test. The results of this study indicate that the average financial ratios are better after the application of ASDM and all data that has been tested is normally distributed. Of the five financial ratios in profitability ratios, all show significant results 0.00 <0.05 so it can be concluded that financial performance after ASDM implementation is better than before ASDM implementation. For the good of the company, the authors suggest that Puskosipa PHS Sumsel can apply the human resource cost accounting method to make the cost of human resources issued is considered not as a burden anymore but made an investment Human Resources. Costs incurred for future periods should continue to be issued for the development of employees in order to provide services to members more professional. Keywords: Financial Performance, Human Resource Accounting